CRIMINAL RESPONSIBILITY FOR PERPETRATORS OF THE CRIMINAL ACT OF UNLOADING IMPORTED GOODS OUTSIDE THE CUSTOMS AREA OR OTHER PLACES WITHOUT PERMIT FROM THE HEAD OF THE CUSTOMS OFFICE - Pratama, Andhika Putra (Inspiring Law Journal, 2025)
Import can be interpreted as the activity of importing goods from one country (abroad) to the customs area of another country. In Indonesia, the source of state revenue consists of tax revenues, non-tax state revenues, and grants. Imported goods carried by passengers, transport crew, or border crossers into the customs area upon arrival must be notified to customs and customs officers, or imported goods sent by post or deposit service may only be issued with the permission of customs and customs officers. Import duty is a levy or import duty on imported goods collected by the Directorate General of Customs and Excise (DJBC). The purpose of this study is to find out how criminal liability for perpetrators of the crime of dismantling imported goods outside the customs area or other places without the permission of the head of the customs office, to find out the factors that affect criminal liability for the perpetrators of the crime of dismantling imported goods outside the customs area or other places without the permission of the head of the customs office, To find out the legal consequences for the perpetrators of the crime of dismantling imported goods in the outside the customs office, to find out the legal consequences for the perpetrators of the crime of dismantling imported goods outside the customs office or other places without the permission of the head of the customs office. The type of research used in this thesis is the normative juridical method.